Pelatihan Kreativitas melalui Penerapan Desain Sederhana Berbahan Termoplastik untuk Siswa SMPK Trimulia Bandung - Suhanjoyo, Shirly Nathania; Aryani, Dewi Isma; Gunawan, Irena Vanessa; Elizabeth, Elizabeth; Royandi, Yudita (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
One of the private institutions in Bandung, Universitas Kristen Maranatha, operates under the tridharma of higher education and the ICE (integrity, care, excellence) values approach. The application of these values is demonstrated in the execution of community service activities by several teaching staff from the Faculty of Fine Arts and Design as material formulators as well as skills trainers/teachers in the form of creativity training through the application of basic thermoplastic designs to Trimulia Junior High School students in Bandung. Through the use of thermoplastics, this activity is meant to help kids develop their artistic creativity. About 100 persons participated in the activity, divided into 4 classes of 25 pupils each with the help of a lecturer and/or a student. This activity can achieve its goal of fostering a knowledge of creativity through creative design thinking by allowing participants to transform the materials in their immediate environment to create things with practical and aesthetic value.